A study on the recovery and characterization of suspended solid from aquaculture wastewater through coagulation/flocculation using chitosan and its viability as organic fertilizer - Benedict Terkula Iber; Donald Torsabo; Chik Che Engku Noramalina Che Engku; Fachrul Wahab; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hassan; Nor Azman Kasan (Journal of Agriculture and Food Research, 2023)
The negative impacts of aquaculture wastewater can best be curtailed by sustainable treatment before discharge. As far as environmental safety is concerned, there is no safer place where floc recovered from the treatment of aquaculture wastewater can be disposed. Therefore, it has become imperative to find a more sustainable way of recycling the floc in a manner that ensures environmental protection and other economic benefits. In the present study, chitosan from Macrobrachium rosenbergii was used in the recovery of floc from shrimp aquaculture wastewater. Optimization of dosage, pH and settling time were performed using RSM where percentage turbidity and TSS removal were tested. Recovered floc was analyzed for plant nutrients and further applied as organic fertilizer for growth enhancement of Water spinach, Ipomea aquatica. Results showed that chitosan removed 92.45% turbidity at 12.5 mg/L dosage and 6.88 pH after 30min. Settling time. Similarly, 69.49% TSS removal was achieved with dosage of 8.75 mg/L at 5.67 pH and 5min. Settling time. The plant nutrient analysis of floc revealed the presence of N, P, K, Ca, Mg Zn, Cu, Mn, Fe, Ni, Se Co Pb, Cr, Al, and As. Furthermore, this study showed that plant treated with floc outperformed other treatments in terms of root volume and length, plant height, leaf count, fresh and dry mass. It was concluded that the nutrients were readily available for the absorption and growth of plants. In addition, the higher growth performance of plants treated with floc was attributed to the higher N level (6.04%) in the floc as compared to other treatments.